The Impact of Anesthetic Agents on Neurocognitive Outcomes in Pediatric Patients - Dandemmanavar, Vinay; KN, Vikas; R, Vinay; Bandyopadhyay, Sukanta; Gakhar, Himanshu; Dey, Animesh (Journal of Neonatal Surgery, 2025)
The impact of general anesthesia on neurocognitive function in pediatric patients remains a topic of growing concern. This study aimed to investigate the short-term and long-term cognitive effects of different anesthetic agents in children undergoing elective non-neurological surgeries. A total of 200 pediatric patients, aged 6 months to 12 years, were enrolled in a prospective observational cohort study and categorized into four anesthesia groups, including propofol, sevoflurane, isoflurane, and multi-agent anesthesia. Neurocognitive assessments were conducted preoperatively and postoperatively at 6 months using standardized tools, including the Bayley Scales of Infant Development (BSID-III), Wechsler Intelligence Scale for Children (WISC-V), and the Child Behavior Checklist (CBCL). The results demonstrated significant cognitive decline associated with volatile anesthetics and multi-agent anesthesia, with the greatest IQ reduction observed in the multi-agent group (-9.1 points) and the least in the propofol group (-3.2 points, p < 0.001). A negative correlation was found between anesthesia duration and IQ decline (r = -0.45, p < 0.001), with an additional 1.2-point IQ reduction per 10-minute increase in exposure time (p = 0.002). Postoperative delirium was highest in the Sevoflurane group (26%), with multi-agent anesthesia (OR: 1.75, p < 0.001) and prolonged anesthesia duration (OR: 1.25, p = 0.002) identified as significant risk factors. These findings highlight the importance of anesthetic agent selection and duration management in minimizing long-term neurocognitive risks. The study suggests that propofol may be a safer option for pediatric anesthesia due to its relatively lower neurocognitive impact. Future research should explore protective strategies and cognitive rehabilitation programs to mitigate anesthesia-related neurodevelopmental impairment.